(untitled) (Journal of Computational Mathematics, 2004)
In this paper we study structured backward errors for some structured KKT systems. Normwise structured backward errors for structured KKT systems are defined, and computable formulae of the structured backward errors are obtained. Simple numerical examples show that the structured backward errors may be much larger than the unstructured ones in some cases.